Free-floating epithelial micro-tissue arrays: a low cost and versatile technique. (10th October 2016) - Flood, P; Alvarez, L; Reynaud, E G
Abstract: Three-dimensional (3D) tissue models are invaluable tools that can closely reflect the in vivo physiological environment. However, they are usually difficult to develop, have a low throughput and are often costly; limiting their utility to most laboratories. The recent availability of inexpensive additive manufacturing printers and open source 3D design software offers us the possibility to easily create affordable 3D cell culture platforms. To demonstrate this, we established a simple, inexpensive and robust method for producing arrays of free-floating epithelial micro-tissues. Using a combination of 3D computer aided design and 3D printing, hydrogel micro-moulding and collagen cell encapsulation we engineered microenvironments that consistently direct the growth of micro-tissue arrays. We described the adaptability of this technique by testing several immortalised epithelial cell lines (MDCK, A549, Caco-2) and by generating branching morphology and micron to millimetre scaled micro-tissues. We established by fluorescence and electron microscopy that micro-tissues are polarised, have cell type specific differentiated phenotypes and regain native in vivo tissue qualities. Finally, using Salmonella typhimurium we show micro-tissues display a more physiologically relevant infection response compared to epithelial monolayers grown on permeable filter supports. In summary, we have developed a robust and adaptable technique for producing arrays of epithelial micro-tissues. This in vitro model has the potential to be a valuable tool for studying epithelial cell and tissue function/architecture in a physiologically relevant context.